Structural and Electronic Responses to the Three Redox Levels of Fe(NO)N2S2‐Fe(NO)2. Issue 60 (9th October 2018) - Ghosh, Pokhraj; Ding, Shengda; Quiroz, Manuel; Bhuvanesh, Nattamai; Hsieh, Chung‐Hung; Palacios, Philip M.; Pierce, Brad S.; Darensbourg, Marcetta Y.; Hall, Michael B.
Abstract: The nitrosylated diiron complexes, Fe2 (NO)3, of this study are interpreted as a mono‐nitrosyl Fe(NO) unit, MNIU, within an N2 S2 ligand field that serves as a metallodithiolate ligand to a dinitrosyl iron unit, DNIU. The cationic Fe(NO)N2 S2 ⋅Fe(NO)2 + complex, 1 +, of Enemark–Feltham electronic notation {Fe(NO)} 7 ‐{Fe(NO)2 } 9, is readily obtained via myriad synthetic routes, and shown to be spin coupled and diamagnetic. Its singly and doubly reduced forms, {Fe(NO)} 7 ‐{Fe(NO)2 } 10, 1 0, and {Fe(NO)} 8 ‐{Fe(NO)2 } 10, 1 −, were isolated and characterized. While structural parameters of the DNIU are largely unaffected by redox levels, the MNIU readily responds; the neutral, S= 1 / 2, complex, 1 0, finds the extra electron density added into the DNIU affects the adjacent MNIU as seen by the decrease its Fe‐ N ‐O angle (from 171° to 149°). In contrast, addition of the second electron, now into the MNIU, returns the Fe‐ N ‐O angle to 171° in1 − . Compensating shifts in FeMNIU distances from the N2 S2 plane (from 0.518 to 0.551 to 0.851 Å) contribute to the stability of the bimetallic complex. These features are addressed by computational studies which indicate that the MNIU in1 − is a triplet‐state {Fe(NO)} 8 with strong spin polarization in the more linear FeNO unit. Magnetic susceptibility and parallel mode EPR results are consistent with the triplet state assignment. Abstract : The remarkable stability of the [Fe(NO)N2 S2 ‐Fe(NO)2 ] species that permits isolation and structural characterization in its three redox levels relates to the delocalization of charge on both Fe(NO) and the Fe(NO)2 support. Subtle shifts of Fe(NO) from the N2 S2 base accommodates a rare, non‐heme {Fe(NO)} 8 triplet state and ca. linear.